2011
DOI: 10.1097/nna.0b013e31822509c4
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Civility in Nursing Education and Practice

Abstract: Incivility in healthcare can lead to unsafe working conditions, poor patient care, and increased medical costs. The authors discuss a study that examined factors that contribute to adverse working relationships between nursing education and practice, effective strategies to foster civility, essential skills to be taught in nursing education, and how education and practice can work together to foster civility in the profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 16 publications
1
45
0
Order By: Relevance
“…To teach new nurses that treating coworkers with civility and respect is as important as treating patients and families, nursing schools need to make this a part of their curriculum, and nursing faculty need to make sure their interactions with students are always civil. 31 …”
Section: Resultsmentioning
confidence: 99%
“…To teach new nurses that treating coworkers with civility and respect is as important as treating patients and families, nursing schools need to make this a part of their curriculum, and nursing faculty need to make sure their interactions with students are always civil. 31 …”
Section: Resultsmentioning
confidence: 99%
“…Uncivil behaviours are perceived as a low‐intensity stress by employees in the course of everyday life, which, however, commonly results in chronic stress, leading negative consequences for the individual and the organisation (Lim & Lee, ). In the health sector, nursing is one of the professions whose members are frequently exposed to workplace incivility (Tunajek, ), which leads to insecure working conditions, low‐quality patient care and increases in medical errors (Clark, Olender, Cardoni, & Kenski, ; McNamara, ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that while "clinical facilitators are expected by universities to be students' advocate, mentor, protector and role-model in healthcare facilities" (p. 6), they frequently failed to meet these expectations, raising concerns about instructor selection and training. Clark, Olender, Cardoni and Kenski [70] stated that "[t]he importance of modeling effective communication and related education to address incivility cannot be underestimated, can reduce its incidence and effects, and can assist in fostering cultures of civility" (p. 325).…”
Section: Faculty Role-modelingmentioning
confidence: 99%